2020
DOI: 10.1159/000507290
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Thyroid and Kidney Function: Analysis from the Korea National Health and Nutrition Examination Survey Between 2013 and 2015

Abstract: Introduction: Thyroid function is evaluated by thyroid stimulating hormone (TSH) and free thyroxine (fT4). Although many studies have indicated an intimate relationship between thyroid hormones and kidney functions, reports about the simultaneous evaluation of TSH and fT4 are rare. Objective: We aimed to analyze the association between TSH and kidney function, with emphasis on a potential nonlinear relationship, and identify an independent relationship between fT4 and kidney function. Methods: We reviewed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
(90 reference statements)
2
10
0
Order By: Relevance
“…14,52,53 It is very important to consider the administration of LVX in patients with CKD and alterations in TSH for a greater benefit in decreasing proteinuria, thus adding the correlation that thyroid hormone in endothelial damage and in cardiovascular risk could also decrease mortality and decrease eGFR. 14,20,52,54 In our study, eGFR increased in the LVX group by 4 ml/min per 1.73 m 2 , compared to that in the placebo group, in which eGFR decreased by 2 ml/min per 1.73 m 2 . Van Welsem et al 9 reported that the normalization of hypothyroidism after treatment with LVX led to a significant improvement in renal function in a patient with CKD.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…14,52,53 It is very important to consider the administration of LVX in patients with CKD and alterations in TSH for a greater benefit in decreasing proteinuria, thus adding the correlation that thyroid hormone in endothelial damage and in cardiovascular risk could also decrease mortality and decrease eGFR. 14,20,52,54 In our study, eGFR increased in the LVX group by 4 ml/min per 1.73 m 2 , compared to that in the placebo group, in which eGFR decreased by 2 ml/min per 1.73 m 2 . Van Welsem et al 9 reported that the normalization of hypothyroidism after treatment with LVX led to a significant improvement in renal function in a patient with CKD.…”
Section: Discussionsupporting
confidence: 41%
“…With TSH levels between 2.5 and 10.0 mIU/ml, we chose TSH >2.5 mIU/ml, as there is evidence that there was an association of a decrease in eGFR 10,54 Q13 with proteinuria, 10 and TSH <10.0 mIU/ml excludes clinical hypothyroidism. All patients treated with angiotensinconverting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs) and without renal replacement therapy who attended the Renal Health Clinic were considered for participation in this pilot clinical trial.…”
Section: Methodsmentioning
confidence: 99%
“…However, others have only reported a positive correlation between free triiodothyronine (FT 3 ) and eGFR [ 15 ]. On the contrary, some studies have found that higher free thyroxine (FT 4 ) was associated with decreased eGFR in the euthyroid population [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Under conditions such as renal hypofunction, it will also have a greater effect on the synthesis, secretion and clearance of thyroid hormones. 2 On the other hand, thyroid hormones significantly impact renal development and kidney dynamics. 3,4 Elevated TSH, FT4, and reduced T3 levels were associated with reduced kidney function.…”
Section: Introductionmentioning
confidence: 99%